GROWTH HORMONE TREATMENT RESPONSE FOR CHILDREN WITH GROWTH HORMONE DEFICIENCY AND TURNER SYNDROME (TS) IN A TERTIARY CARE CENTER - Leong, Annie; Wong, SL Jeanne; Selveindran, Nalini M; Tee, Pian Pian; Cheng, Hooi Peng; Gan, Cheng Guang; Teik, Teoh Sze; Amin, Arliena; Hong, Janet YH (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Recombinant growth-hormone (rhGH) has been widely used to treat a variety of growth disorders. Although responses are generally satisfactory, evidence is increasing for a high rate of poor or unsatisfactory response. This study aimed to evaluate the growth response to rhGH therapy in the patients in our tertiary centre and identify the poor responders. METHODOLOGY This is a cross-sectional study based on medical records of the patients still on rhGH in year 2019-2020. The growth parameters and rhGH doses recorded throughout the treatment were retrieved. Poor response was defined as first-year increment in height standard-deviation-score (SDS) <0.5 for patients with severe growth hormone deficiency (GHD) or <0.3 for other diagnoses. RESULTS Thirty-five patients were included in the study with 20 (57%) diagnosed with GHD and 15 (43%) with Turner syndrome (TS). Majority of the patients with GHD had severe organic GHD with peak GH level <5 µg/ml (52.4%). Most presented with significant short stature with height SDS of -4.15 ± 1.32 on initiation of treatment. The first-year height velocity (HV) was 10.0 ± 3.1 cm/year (3.42 ± 2.66 SDS) with median height increment of 0.74 (-0.57-2.83 SDS). The subsequent years, HV remained steady with average of >6 cm/year (0.62-2.94 SDS). The patient with Turner Syndrome had a starting height of -3.52 ± 1.05 SDS. The first year HV was 7.5 ± 1.4 cm/ year (1.65 ± 1.95 SDS) with median height increment of 0.31 (-1.32-0.74 SDS). HV for the subsequent years was on average 4-5.5cm/year (-2.51-0.61 SDS). The average rhGH doses was 0.033 ± 0.003 mg/kg/day for patients with GHD and 0.046 ± 0.004 mg/kg/day for patients with TS. Poor responders comprised 19% of patients with GHD and 21.4% of patients with TS. CONCLUSION Patients with severe GHD generally responded better to rhGH therapy as compared to those with idiopathic GHD and TS. Awareness, recognition, and management of poor response to growth-promoting therapy will lead to better patient care, greater cost-effectiveness and improved clinical benefit.